Pengaruh Kepercayaan, Biaya Transaksi dan Kenyamanan Terhadap Keputusan Pedagang Menggunakan QRIS Sebagai Sistem Pembayaran Digital - Chairiel Oktaviar; Dhani Iramawan; Harefan Arief (Journal of Fundamental Management (JFM), 2025)
In the era of rapid digitalization, the need for a fast, easy, cheap, safe and reliable payment system is becoming increasingly important. The Quick Response Code Indonesian Standard (QRIS), launched by Bank Indonesia, is here as an innovative solution to support non-cash transactions in various economic sectors. In its use, there are 3 (three) main aspects that are of concern to the public and business actors, namely the level of trust, the amount of transaction costs, and the convenience of QRIS users. In addition, the number of merchants, both street vendors and managed MSMEs who use and accept QRIS as a non-cash (digital) payment tool has also grown rapidly. According to data sources from Bank Indonesia (BI) until the end of the first quarter of 2025 (March 2025), QRIS consumer users reached 56.3 million people, while the number of Merchants (QRIS Receiving Merchants) was 38.1 million, most of which were MSMEs. Bank Indonesia is targeting that by the end of 2025 the number of QRIS consumer users will reach 58 million. The figures above show the large penetration and market share of QRIS in Indonesia both in terms of consumer users and merchants, this phenomenon indicates that the trust variable, transaction cost variable and convenience variable have a positive and significant effect on the increase in the number of consumers and merchants using QRIS, this proves that the adoption process of non-cash (digital) payment systems using QRIS is increasingly massive and inclusive until the end of the first quarter of 2025 (March 2025).